Engineering reactors for catalytic reactions - Ranade, Vivek V. (Journal of Chemical Sciences, 2014)
Catalytic reactions are ubiquitous in chemical and allied industries. A homogeneous or heterogeneous catalyst which provides an alternative route of reaction with lower activation energy and better control on selectivity can make substantial impact on process viability and economics. Extensive studies have been conducted to establish sound basis for design and engineering of reactors for practising such catalytic reactions and for realizing improvements in reactor performance. In this article, application of recent (and not so recent) developments in engineering reactors for catalytic reactions is discussed. Some examples where performance enhancement was realized by catalyst design, appropriate choice of reactor, better injection and dispersion strategies and recent advances in process intensification/ multifunctional reactors are discussed to illustrate the approach.
21st National Symposium on Catalysis (CATSYMP), CSIR Indian Inst Chem Technol, Hyderabad, INDIA, FEB 11-13, 2013
Keywords: Catalyst; effectiveness; engineering; hydrodynamics; reactors